Orbital Apex Syndrome in an Uncontrolled Diabetes Mellitus Patient: Case Report - Astriani Rahayu; Olivia Putri Chairunnisa; Muhammad Yusran (Medula, 2026)
Orbital Apex Syndrome (OAS) is a rare and severe neurological condition characterized by dysfunction of multiple cranial nerves, including II, III, IV, V1, and VI, which can rapidly progress and lead to permanent vision loss. This report describes a case of a 63-year-old male with uncontrolled diabetes mellitus, hypertension, and gout arthritis who presented with left periorbital pain, swelling, redness, followed by vision loss and ophthalmoplegia. Clinical examination revealed no light perception, severe ptosis, proptosis, reduced corneal sensation, and a relative afferent pupillary defect in the left eye. Laboratory findings showed leukocytosis and markedly elevated HbA1c levels. Brain computed tomography demonstrated opacification of the left ethmoid and sphenoid sinuses with enhancement at the left orbital apex, supporting the diagnosis of OAS secondary to bacterial sinusitis. Despite prompt clinical evaluation and planned further imaging, the patient’s systemic condition rapidly deteriorated, leading to multi-organ failure and death before neurological improvement could be achieved. This case highlights the aggressive course of OAS in immunocompromised individuals, particularly those with poorly controlled diabetes. Inflammation and edema at the orbital apex can cause compression of multiple cranial nerves, resulting in visual impairment, ophthalmoplegia, and sensory deficits. Early recognition of symptoms, rapid diagnosis, and immediate multidisciplinary management, including targeted antimicrobial therapy and strict glycemic control, are essential to prevent irreversible complications and improve outcomes. OAS secondary to sinusitis should be strongly considered in patients presenting with painful ophthalmoplegia and visual loss, especially in those with significant metabolic comorbidities.